Eksistensi Taksi Online pada Kawasan Pariwisata di Bali - I Ketut Adnyana; Ida Ayu Putu Widiati; I Nyoman Sutama (Fakultas Hukum Universitas Warmadewa, 2019)
The economic growth of a nation depends greatly on the quality of transportation. Online taxi is an innovation in public transport. Using communication technology in the form of applications that can connect between users with transport driver. The existence of a taxi online growing rapidly due to public transport users got options other than conventional taxis. But the presence of a taxi online got rejection in the society especially by society as the transport trade, because the rated breaking traffic laws and road transport as well as going on unhealthy business competition. There are two (2) problems of research: (1) legal online taxi arrangements according to the law No. 22 of 2009, (2) the existence of a taxi online at Bali's tourism regions. The purpose of this research is to know the law setting the online presence and existence of taxi online on the area of tourism in Bali.This research uses the normative legal research methods with the application of laws or regulations, the study of librarianship as primary and secondary legal materials and supported by empirical data with interviews directly. Based on the results of the research note that: (1) online Taxi is not mentioned explicitly in the Act No. 22 of year 2009, but the taxi online is set in the regulation of the Minister of transportation Number 108 Years 2017, as the rental of special transport. (2) A taxi online still got rejections due to its perceived would happen competition and do not respect the role of the community in the area of tourism. The role of local governments in regulating taxi online presence is very important, so as not to give rise to polemics which can interfere with the image of Bali tourism.